Anti-Bacterial Effect of Zanthoxylum armatum Oleoresin Against Some Bacterial Isolates from Pork and Chicken Meat Sold in Dharan, Nepal - Rai, Suman; Rai, Shiva Kumar (Himalayan Journal of Science and Technology, 2017)
Zanthoxylum armatum is a medicinal plant found in the Himalayan range. The present study was carried out to unravel the antimicrobial activities of Z. armatum oleoresin against bacteria isolated from raw pork and chicken meat sold in Dharan submetropolitan city. Five bacterial species Salmonella enterica var Typhi, Escherichia coli, Shigella dysenteriae, Bacillus cereus and Staphylococcus aureus were isolated. The antimicrobial activity of oleoresin extracted from Z. armatum was tested by agar well diffusion method and MICs were compared with standard antibiotics against isolated bacteria. The MIC values of oleoresin were ranged from 25-75 μl/mL. Zone of inhibition for oleoresin extracted with acetone was 10 mm (25 μl/mL) against Shigella dysenteriae and Staphylococcus aureus, and 9.5mm (25 μl/mL) against Escherichia coli respectively. Zone of inhibition of oleoresin extracted with chloroform was 12 mm (25 μl/mL) and 11 mm (25 μl/mL) against Escherichia coli and Staphylococcus aureus respectively, that of oleoresin extracted with cyclohexane was 10mm(25 μl/mL and 50 μl/mL) against all the isolates, except Bacillus cereus. Zone of inhibition of oleoresin extracted with methanol was 10mm (25 μl/mL) and 9.5 cm (25 μl/mL) against Shigella dysenteriae and Bacillus cereus and Escherichia coli respectively. Zone of inhibition of oleoresin extracted with petroleum ether was 10 mm (25 μl/mL and (50 μl/mL) against Escherichia coli and all the isolates except Escherichia coli. Increasing oleoresin concentrations showed greater antimicrobial effect on the isolates. Bacillus cereus was most affected; comparatively, Salmonella enterica var Typhi was least affected by all the antibiotics.